The Dark Triad, Moral Disengagement, and Social Entrepreneurial Intention: Moderating Roles of Empathic Concern and Perspective Taking - Wu, Wenqing; Su, Yuzheng; Huang, Xuan; Liu, Wenyi; Jiang, Xin (Frontiers in Psychology, 2020)
Past research about social entrepreneurial intention has centered on the impact of bright personalities; however, dark personalities such as the dark triad are also considered to have advantages. This study explored the relationship between the dark triad and social entrepreneurial intention by focusing on the mediating role of moral disengagement and the moderating role of empathic concern and perspective taking. Based on a sample of 491 undergraduates and 412 students in a Master in Business Administration program in China, the dark triad was found to be negatively related to social entrepreneurial intention through moral disengagement. Moreover, high levels of empathic concern and perspective taking weakened the direct effect of the dark triad on moral disengagement as well as the indirect effect of the dark triad on social entrepreneurial intention. Our study extends the research in the field of personality and entrepreneurship. Given the findings on the role of moral disengagement, empathic concern, and perspective taking, education efforts may assist in decreasing the negative effects of the dark triad on social entrepreneurial intention.